Use of waste from civil construction in repairs of rural roads - Rodrigues, Rivelino; Kozusny-Andreani, Dora Inés; Frias, Danila Fernanda Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The objective of the work is to verify the feasibility of the use of solid waste from the construction industry for the maintenance of rural roads. Data were collected correlating with the production and destination of RCC in the municipality. It was noted that there are approximately 50 kilometers of rural roads that present very bad traffic conditions during the rainy season. Therefore, a 350-meter, was paved, resulting in an RCC value of R$27.00/m³. If using stone crushed stone to perform the same paving, a cost of R$ 76.00/m³. The application of the RCC in the pavement of the section of the selected rural road presented solution for two serious problems that the residents of the municipality currently have (adequate destination for the rubble generated and improvements of the conditions of use of the roads on land, optimizing the flow of agricultural production and the local economy). In this way, the use of construction waste, generated in the city of Jales – SP, for the maintenance of rural roads of the municipality presented environmental and economic viability.